2004
DOI: 10.1111/j.1440-1843.2004.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

Protease inhibitor phenotypes and serum alpha‐1‐antitrypsin levels in patients with COPD: A study from Hong Kong

Abstract: The low prevalence of deficiency Pi phenotypes/subtypes suggests a lack of contribution of alpha1-AT deficiency to the pathogenesis of COPD in Chinese patients. The strategy of launching an alpha1-AT deficiency detection program among COPD patients, based on the recommendation of the World Health Organization, may not be readily applicable in our local setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Therefore, high levels of free THBG offer a basis for its involvement in other biological processes. In this study, A1AT (SERPINA1) was not altered, which was in accordance with previous studies among Chinese patients,39 but THBG (SERPINA7) was elevated in COPD patients. Therefore, it was considered worthwhile to further explore the potential clinical and biological value of THBG in patients with COPD.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, high levels of free THBG offer a basis for its involvement in other biological processes. In this study, A1AT (SERPINA1) was not altered, which was in accordance with previous studies among Chinese patients,39 but THBG (SERPINA7) was elevated in COPD patients. Therefore, it was considered worthwhile to further explore the potential clinical and biological value of THBG in patients with COPD.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies identified mean values or reference intervals of AAT serum concentration but they were limited to target groups, mostly COPD cases or populations in which the frequency of AATD is low, such as Japanese19 and Korean populations,20 or in patients with a peculiar clinical phenotype, such as Peyronie's disease,21 or characteristic cohorts, such as paediatric subjects7 and pregnant women 22. The use of advanced technologies makes this study innovative.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuse et al (1995), Shim (2001) and Kim et al (2005) did not find a significant association between PiM1, PiM2 or PiM3 alleles and COPD, whereas Kwok et al (2004) came across a significant increase in PiM1M3, PiM2M3 phenotypes and Gupta et al (2005) reported a significant increase for the PiM3 allele in COPD patients.…”
mentioning
confidence: 73%